Effectiveness of structured teaching programme on knowledge regarding selected behavioral disorders in school children among primary school teachers of selected schools at Udaipur, Rajasthan - Soni, Jayesh; Kumar Menaria, Dashrath; Pratap Singh, Divya (International Journal of Nursing Research, 2023)
Worldwide the behavioral disorders such as mania, anxiety, aggressiveness, agitation, delusions, alogia, phobia, affect labiality, and apathy is raised day by day. Aim: A pre-experimental one group pre-test post-test design to assess the effectiveness of structured teaching programme on knowledge regarding selected Behavioral disorders in School children among Primary school Teachers of selected schools at Udaipur Rajasthan. Materials and methods: A standardized tool was used for data collection which was validated by the experts. The consisting of 60 primary school teachers in selected schools at Udaipur by using purposive sampling technique method. The tool comprised of using structured questionnaire. The pre-test was conducted and the structured teaching programme administered. The collected data were analyzed with descriptive statistics using frequency, percentage, mean and inferential analysis using “chi-square” test. Results: The result showed that the mean post-test knowledge score is 22.5 (75%) is greater than the mean pre-test knowledge score 8 (26.7%). The above table also depicts that the enhancement in the knowledge of participants is 14.5 (48.3%) supporting the post-test knowledge score are higher than the pre-test knowledge score. The data further represent that the„t‟ value of 28.43 is significantly higher than the tabular value 2.00 at 0.05 level of significance. Conclusion: The structured teaching programme was significantly effective in increasing the knowledge regarding selected Behavioral disorders in School children among Primary school Teachers. The mean difference 14.5 between pre-test and post-test knowledge score of the Primary school Teachers was found to be significant